FUNDAMENTAL AND CLINICAL STUDIES ON RBL25000 (CLAVULANIC ACID-AMOXICILLIN) IN THE FIELD OF DERMATOLOGY - KASHIWA, NAOHIRO; IKEDA, MASAMI; NOHARA, NOZOMI; SUWAKI, MASAO (CHEMOTHERAPY, 1982)
BRL25000, a newly developed antibiotic formulation of amoxicillin and clavulanic acid, was studied experimentally and clinically in the field of dermatology. The following results were obtained. 1) The in vitro antibacterial activity of amoxicillin alone and in combination with clavulanic acid against S. aureus and S. epidermidis was studied. Most strains of both Staphylococci were inhibited by 3.13μg/ml or less of amoxicillin in combination with clavulanic acid. Two to fivefold reductions in MICs for amoxicillin resistant strains were observed for amoxicillin in combination with clavulanic acid than with amoxicillin alone. 2) Serum and skin levels of amoxicillin and clavulanic acid in rats were studied after oral administration of BRL25000. The serum and skin levels of amoxicillin and clavulanic acid increased evenly. 3) Twenty-eight patients with various skin infections (furuncles 9, furunculosis 5, inflammatory atheroma 2, secondary infection 6, paronychia 3, abscess 1, lymphangitis 2) were treated with BRL 25000 orally at a total dosage of 1, 125mg administered t. i. d. or 1, 500mg administered q. i. d. Favourable clinical results were obtained in 24 (85.7%). Side effects were found nausea in 1 and gastro-intetinal disorders in 4 which were not so severe.